The Problem of Good and Evil in the World According to the Philosophical Teachings of Avecinna - Kutibaeva Elizaveta, Yuldasheva Govkherjan, Mukhitdinova Firyuza Abdurashidovнa (International Journal of Advanced Science and Technology, 2020)
The article discusses the teachings of Ibn Sina on the development and perfection of an individual in a globalised society, as well as the relevance of these ideas in the fight against coronavirus where stress and panic harm to human health put forward by Avicenna. The author studied Avicenna’s medical ideas, as well as the concept of "perfect man", about the social essence of man, forms and means of education and personality in the ideal state of Avicenna Keywords: medicine stress, fear, panic, idea, science, society, personality, coronavirus, countries, quarantine.